Pengembangan Media Pop Up Book Digital Untuk Meningkatkan Kemampuan Komunikasi Siswa Pada Mata Pelajaran IPAS Sekolah Dasar - Mar’atush Sholiha; Atikah Syamsi; Nur Atikoh (Journal of Humanities, Social Sciences, and Education, 2025)
This research aims to develop a learning media in the form of a digital pop-up book to enhance the communication skills of elementary school students in the subject of IPAS. Communication skills are important to instill from an early age as they are related to the self-confidence and social relationships of students with both peers and teachers. The digital pop-up book medium was chosen due to its visual, audio, and animation advantages that can attract learning interest and provide an interactive learning experience. The research method used is Research and Development (R&D) with the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. The media was developed using PowerPoint and Canva, and then validated by experts in content, media, and language. Implementation was carried out at SDN Dukuh Semar 1 in Cirebon City with subjects from grade IV. The validation results show that this media is very suitable for use, with a feasibility percentage of 78-87%. The media is not only visually and content-wise appealing, but also encourages students to actively speak and express their opinions. The Wilcoxon test results indicated a significance value of 0.000, indicating a significant difference between the pre-test and post-test. The N-Gain test shows an average improvement of 0.77 (high category), proving the effectiveness of the media in enhancing students' communication skills.